A Profile Study of Elderly Offenders in the Community Criminal Courts of Singapore: Theorizing Geriatric Criminality - Narayanan, Ganapathy (International journal of offender therapy and comparative criminology, 2024)
This research, using data from the Community Criminal Courts where a majority of elderly offenders are tried and sentenced, investigates the socio-economic profile of elderly offenders and the factors influencing their criminal motivation in Singapore. It revisits conceptualizations of offending in older age which until now has received scant attention even in Asian societies where ties to conventional institutions are thought to be “protective.” The majority of elderly offenders in this study were “revolving door prisoners” and were never in possession of any efficacious social capital that would have prevented them from committing a crime or enabled their re-entry process, a problem compounded by the study’s findings that almost 70% of the sampled offenders had experienced mental health issues. This would have spelled adverse consequences for their desistance and, conversely, their recidivist behavior, a finding that was consistent with many other studies that had examined the association between psychosis and crime.